2023
DOI: 10.1177/00952443231212553
|View full text |Cite
|
Sign up to set email alerts
|

Tensile creep behavior and structures of sisal fiber reinforced styrene butadiene thermoplastic elastomer/polystyrene composites

Yuxin Liu,
Liangyan Liao,
Zesheng Liang
et al.

Abstract: Styrene butadiene thermoplastic elastomer (SBS)/polystyrene (PS)/sisal fiber (SF) composites were prepared by melt-blending method. The tensile creep behavior of SBS/PS/SF composites was studied and fitted by four viscoelastic models including Findley, Burger, generalized Kelvin-Voigt and Maxwell models. The effects of content and surface properties of SF treated by alkali and silane coupling agent on the creep behavior, structures and thermal properties of the composites under the action of tensile stress wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…5,6 Among the block copolymers containing PS segment, the most well-known one used as a thermoplastic elastomer is styrene-butadiene-styrene block copolymer, known as SBS. [7][8][9] Wu et al investigated the effect of use of SBS on the toughening of a blend of polyethylene (PE) and PS. They found that adding 15 wt% SBS to the blend of PS/PE blend with a ratio of 4/1 enhanced the impact strength by approximately 15 times.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Among the block copolymers containing PS segment, the most well-known one used as a thermoplastic elastomer is styrene-butadiene-styrene block copolymer, known as SBS. [7][8][9] Wu et al investigated the effect of use of SBS on the toughening of a blend of polyethylene (PE) and PS. They found that adding 15 wt% SBS to the blend of PS/PE blend with a ratio of 4/1 enhanced the impact strength by approximately 15 times.…”
Section: Introductionmentioning
confidence: 99%
“…Some fibers effectively employed as reinforcements in thermoplastic and thermoset matrices are hemp, jute, kenaf, flax, ramie, and sisal. [15][16][17][18][19][20][21][22][23] Hemp is one of the challenging fibers due to it can improve the mechanical properties and rigidness of the final product. Therefore, it has an enormous potential to be used as a reinforcement in composite materials.…”
Section: Introductionmentioning
confidence: 99%